2007
DOI: 10.1016/j.ejvs.2007.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 1% and 3% Polidocanol Foam in Ultrasound Guided Sclerotherapy of the Great Saphenous Vein: A Randomised, Double-Blind Trial with 2 Year-Follow-up. “The 3/1 Study”

Abstract: This study demonstrates equivalent efficacy for 1% POL and 3% POL foam in sclerotherapy of the GSV where the trunk is less than 8 mm in diameter. These data obtained two years of follow-up confirm our previously reported 6 month-follow-up data published in 2005.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(23 citation statements)
references
References 16 publications
0
22
0
Order By: Relevance
“…Although there are no published outcomes studies of Varisolve ® comparing polidocanol concentrations, two studies have compared outcomes in sclerotherapy treatment of great saphenous vein reflux using air-based 1% and 3% polidocanol foam in either 80 [34] or 148 [35] patients. At long duration after treatment (one year or greater), both studies revealed equivalent efficacy for the two doses to abolish reflux.…”
Section: Clinical Efficacymentioning
confidence: 99%
“…Although there are no published outcomes studies of Varisolve ® comparing polidocanol concentrations, two studies have compared outcomes in sclerotherapy treatment of great saphenous vein reflux using air-based 1% and 3% polidocanol foam in either 80 [34] or 148 [35] patients. At long duration after treatment (one year or greater), both studies revealed equivalent efficacy for the two doses to abolish reflux.…”
Section: Clinical Efficacymentioning
confidence: 99%
“…6 While foam sclerotherapy does obviate the necessity for tumescent anaesthesia, efficacy rates are lower than endothermal ablation and reported complication rates are higher. 7,8 At present, it cannot be stated that foam sclerotherapy is as efficacious as endothermal ablation.…”
Section: Introductionmentioning
confidence: 99%
“…Frullini and Cavezzi showed foam sclerotherapy is equally applicable in complicated and uncomplicated venous disease (19). Rapid healing of ulcers following foam sclerotherapy was reported in some clinical researches and it confirmed that this treatment could probably achieve the same outcomes that result from saphenous obliteration in leg ulcer patients (20)(21)(22)(23)(24)(25)(26)(27).…”
Section: Discussionmentioning
confidence: 85%